2020
DOI: 10.1002/cjp2.158
|View full text |Cite
|
Sign up to set email alerts
|

NTRK fusions in osteosarcoma are rare and non‐functional events

Abstract: Neurotrophic tyrosine receptor kinase (NTRK) fusions are promising molecular targets that have been described in a broad range of malignant tumours. Fusions commonly lead to the expression of chimeric proteins with constitutive tyrosine kinase activation that drives tumorigenesis. Despite a low prevalence among most solid tumours (<1%), the first encouraging results with pan-NTRK tyrosine kinase inhibitors (TKIs) such as larotrectinib or entrectinib stimulated the search for eligible patients. Here, we report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 15 publications
1
16
0
1
Order By: Relevance
“…Novel structural variants involving gene kinases need to be confirmed at the RNA level to exclude random or non‐transcribed events. In this respect, one recent study identified NTRK fusions by DNA‐based NGS in rare osteosarcoma cases, however, these abnormalities lacked functional impact, suggesting that treatment approaches using pan‐NTRK TKIs in this setting are unlikely to benefit these patients, as these fusions likely represent randomly occurring passenger alterations 27 . Moreover, based on accumulated sequencing data, sarcomas characterized by complex genomics are less likely to harbor kinase gene fusions as driver events 28…”
Section: Discussionmentioning
confidence: 99%
“…Novel structural variants involving gene kinases need to be confirmed at the RNA level to exclude random or non‐transcribed events. In this respect, one recent study identified NTRK fusions by DNA‐based NGS in rare osteosarcoma cases, however, these abnormalities lacked functional impact, suggesting that treatment approaches using pan‐NTRK TKIs in this setting are unlikely to benefit these patients, as these fusions likely represent randomly occurring passenger alterations 27 . Moreover, based on accumulated sequencing data, sarcomas characterized by complex genomics are less likely to harbor kinase gene fusions as driver events 28…”
Section: Discussionmentioning
confidence: 99%
“…Although a lot of research is done on soft tissue tumors, little is known about the role of NTRK fusions in bone sarcomas. A very interesting study revealed three osteosarcoma samples with non-functional NTRK fusions [ 32 ]. In the first case, an NTRK2-UFD1 fusion was identified.…”
Section: Histopathology Of Sarcomas Showing Ntrk mentioning
confidence: 99%
“…So legen beispielsweise mehrere Berichte zu ALK(anaplastische Lymphomkinase)-positiven Lungenkarzinomen nahe, dass Translokationen mit verschiedenen Fusionspartnern und Bruchpunkten unterschiedliche biologische Eigenschaften aufweisen [ 68 ] und mit unterschiedlichen klinischen Therapieverläufen assoziiert [ 8 , 37 ] sein können. Bei genetisch komplexen Tumoren, nachgewiesen bei Osteosarkomen, können NTRK -Fusionen auch zu nichtfunktionalen Genprodukten führen [ 3 ].…”
Section: Ntrk -Genfusionen Als Onkogene Treiberunclassified